What is currently known about endometrial cancer in Lynch syndrome? - review - Kwiatkowska, Agnieszka; Krawczyk, Dominika; Kułak, Krzysztof; Makuch, Sylwester; Sapko, Klaudia (Journal of Education, Health and Sport, 2019)
Introduction: About 5% of endometrial cancer cases can be genetic and inherited. Lynch syndrome, also called hereditary non-polyposis colorectal cancer (HNPCC), is an autosomal dominant syndrome. Caused by a germline mutation in one of the DNA mismatch repair genes, it is responsible for most hereditary cases. Lynch syndrome is associated with the early onset and the development of many types of cancer, especially colon and endometrial cancer.Methods: The review of publications regarding Lynch syndrome-associated endometrial cancer and methods for screening, diagnosis and its prevention.State of knowelage: Endometrial cancers related to Lynch syndrome are mostly sentinel (they reveal the predisposition in 50% of families) and are characterized by young age at onset (commonly before 60 years). The lifetime cumulative risk of endometrial cancer for women with Lynch syndrome is about 40% to 60%, which equals or exceeds their risk of colorectal cancer. Lynch syndrome, the current gynecologic cancer screening guidelines include annual endometrial sampling and transvaginal ultrasonography beginning at age of 30-35 years, which is very important in the early detection of this cancer. Risk-reducing surgery consisting of prophylactic hysterectomy and bilateral salpingooophorectomy should be offered to women aged 35 years or older who do not wish to preserve their fertility.Summary: Diagnosis of endometrial cancer in patients with Lynch syndrome has important clinical implications for the individual and family members.